The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1038/srep03197
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic speciation or global spread? The case of a cosmopolitan marine invertebrate with limited dispersal capabilities

Abstract: The existence of globally-distributed species with low dispersal capabilities is a paradox that has been explained as a result of human-mediated transport and by hidden diversity in the form of unrecognized cryptic species. Both factors are not mutually exclusive, but relatively few studies have demonstrated the presence of both. Here we analyse the genetic patterns of the colonial ascidian Diplosoma listerianum, a species nowadays distributed globally. The study of a fragment of a mitochondrial gene in locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 58 publications
(81 reference statements)
1
22
2
Order By: Relevance
“…This is in contrast to other studies on mites, insects, or other invertebrates, which have shown that presumed widespread taxa often represent complexes of cryptic species (Cicconardi, Fanciulli, & Emerson, 2013; Navia et al, 2013; Pérez-Portela, Arranz, Rius, & Turon, 2013; Schäffer et al, 2010). However, a clear geographic pattern can be seen in the haplotypes, which means that populations from different geographic locations do not show extensive gene flow between each other and dispersal may be limited.…”
Section: Discussioncontrasting
confidence: 93%
“…This is in contrast to other studies on mites, insects, or other invertebrates, which have shown that presumed widespread taxa often represent complexes of cryptic species (Cicconardi, Fanciulli, & Emerson, 2013; Navia et al, 2013; Pérez-Portela, Arranz, Rius, & Turon, 2013; Schäffer et al, 2010). However, a clear geographic pattern can be seen in the haplotypes, which means that populations from different geographic locations do not show extensive gene flow between each other and dispersal may be limited.…”
Section: Discussioncontrasting
confidence: 93%
“…The sequences generated for Clavelina lepadiformis corresponded to the introduced Atlantic clade defined in Turon et al ( 2003 ). All sequences obtained for Diplosoma listerianum corresponded to clade A (Pérez-Portela et al 2013 ), sequences for C. intestinalis matched species A described in Caputi et al ( 2007 ) and Nydam and Harrison ( 2007 ), and sequences for B. schlosseri corresponded to clade 5 in López-Legentil et al ( 2006 ), except for KF309545 that matched clade 1, and two sequences (KF309592, KF309530) that presented 98 % identity (BLASTn) with a USA specimen (GU065352, Callahan et al 2010 ). Identification of Ascidiella scabra and A. aspersa was made based on morphological characters following a recent review (Nishikawa et al 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, marine species live in a dispersive environment and there is a large number of cryptic, co-existing native and non-native marine species (e.g. in tunicates; Bock et al 2012;Perez-Portela et al 2013). Furthermore, the increasing rate of marine biological invasions on the global scale facilitates numerous secondary contacts between allopatric taxa (Geller et al 2010).…”
Section: Introductionmentioning
confidence: 99%